Eco-Friendly Sustainable Synthesis of Graphene Quantum Dots from Biowaste as a Highly Selective Sensor - Abbas, Aumber; Liang, Qijie; Abbas, Saleem; Liaqat, Maryam; Rubab, Shabnum; Tabish, Tanveer A. (Nanomaterials (Basel, Switzerland), 2022)
Graphene quantum dots (GQDs) have generated a great deal of scientific interest due to their bright fluorescence, good biocompatibility, minimal toxicity and fascinating physicochemical features. However, the ultimate issues regarding the acidic contaminations and high synthesis cost of GQDs remain open challenges for their real-world applications. Herein, we report an eco-friendly, acid-free and sustainable method for the preparation of GQDs using a cost-efficient, and renewable carbon source, ‘biomass-waste’, which simultaneously solves the risk of contamination from strong acids and high expenditure initiated by expensive precursors. The results demonstrate that GQDs possess a size range of 1–5 nm with an average size of ~3 ± 0.4 nm and a thickness of ~1 nm consisting of 1–3 layers of graphene. As-prepared GQDs demonstrate fascinating size-dependent optical properties and considerable surface grafting. Due to their intriguing optical properties, these GQDs are employed as fluorescence probes to detect ferric ions. A focused and sensitive sensor is developed with a detection limit down to 0.29 µM. This study emphasizes the need for using a reasonably green process and an inexpensive biomass precursor to create high-value GQDs that hold great potential for use in photocatalytic, bioimaging and real-world sensing applications.